Quality of life among women with breast cancer ffrom Universiti Kebangsaan Malaysia Medical Centre, Malaysia - A.A Redhwan; M.N Md. Idris; M.I Zaleha; C Robert; I Fuad; R.A Sami (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : The purpose of this study was to determine the quality of life (QOL) of breast cancer survivors based on socio-demographic and clinical characteristics. Methods : A cross-sectional study was performed on 125 breast cancer survivors from the outpatient clinics. FACT-B (Functional Assessment of Cancer Therapy-Breast) questionnaire was used to assess survivors’ QOL. Results : Survivors with low body mass index (BMI) (underweight) were found to have the lowest overall QOL. Those who were overweight had a higher overall QOL, and those who were normal-weight had the highest QOL. Low educational level, being underweight and low monthly household income were significantly associated with lower overall QOL Tamoxifen use and employment status were significantly associated with QOL in some domains. Time since diagnosis to QOL interview was significantly associated with greater scores in emotional well-being (EWB). Multiple linear regression indicated that age, marital status, monthly household income, surgery and histological grade were indicative of the patients QOL. Conclusion : The four primary factors related to better QOL were high educational level, high income, normal body weight and greater duration from the time of diagnosis to the time of interview. Age, marital status, income, lumpectomy and histological grade were indicative of the patient QOL.